Assessing the Effectiveness of Vocational Education and Training (TVET) in Preparing Students for the Workforce in Liberia - Atul Khajuria; Stephen Monday; Christian Gendemeh; J. Samuel Kamanda4 (Recent Trends in Social Studies, 2025)
Training in Vocational and Educational Training (TVET) is important for students as it enables them to gain practical skills for employment. In Liberia, the main concern of TVET programs is the increasing supply needs for skilled workers in different industries Liberian industries. This research seeks to explore the effectiveness of these programs in Liberia in relation to employment and self-employment opportunities from the 833 respondents distributed across various TVET institutions. For Methods, A well-structured Likert scale questionnaire was used to collect data from the 833 respondents who completed TVET programs in Liberia. Some of the issues surveyed included pertinence of curriculum, quality of practical training offered, follow-up services, and partnership with employers. The data was processed by employing descriptive and inferential statistical analysis to identify patterns and relationships between and among the variables. In Results, A good proportion of the respondents, which is about 70%, indicated that indeed the TVET curriculum is relevant to the demands of the labor market requirements. On the contrary, 60% of the participants noted that there were limited opportunities for practical training components like internships. Around 55% of the respondents were able to get jobs within six months post-graduation, and 40% could start their own enterprises Employers reported being moderately satisfied (65%) with the skills of TVET graduates albeit with an emphasis on the lack of soft skills like communication and problem-solving skills In Conclusion, TVET programs in Liberia have a moderate effectiveness in equipping learners with job readiness skills, especially regarding the relevance of the curriculum to work and employment after school. However, the research points out insufficient practical work experiences and soft skill training. As a response, the TVET providers are encouraged to strengthen partnerships with employers to create more internship and train students in soft skills to align with industry needs.
Keywords: Liberia; TVET; Training; Vocational education; employer satisfaction; employment outcomes; skills development; workforce preparation